2017
DOI: 10.2147/ndt.s132511
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parental affectionless control is associated with high neuroticism

Abstract: ObjectiveDepressed patients are prone to perceive that they were exposed to affectionless control by parents. Meanwhile, high neuroticism is a well-established risk factor for developing depression. Therefore, this study examined whether perceived parental affectionless control is associated with high neuroticism.MethodsThe subjects were 664 healthy Japanese volunteers. Perceived parental care and protection were assessed by the Parental Bonding Instrument. Parental rearing was categorized into either optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
5
16
0
Order By: Relevance
“…This result is consistent with the studies in European and Latin American countries despite the difference in the cultural and social characteristics [12,16]. In another study carried out in Japan, subjects who experienced "paternal affectionless control" displayed less ability to adapt with anxiety and stress, leading to mental disorders in these individuals [23]. The attachment theory of Bowlby underscores that ine cient parental style such as excessive control can make children more prone to mental disorders [11].…”
Section: Discussionsupporting
confidence: 86%
“…This result is consistent with the studies in European and Latin American countries despite the difference in the cultural and social characteristics [12,16]. In another study carried out in Japan, subjects who experienced "paternal affectionless control" displayed less ability to adapt with anxiety and stress, leading to mental disorders in these individuals [23]. The attachment theory of Bowlby underscores that ine cient parental style such as excessive control can make children more prone to mental disorders [11].…”
Section: Discussionsupporting
confidence: 86%
“…Subsequent studies show that parental rearing evaluated by the PBI is related to psychiatric disorders such as major depression, obsessive-compulsive disorder, and eating disorders. [3][4][5][6][7] With regard to other aspects, our studies suggest that anomalous parenting as assessed by the PBI is associated with some personality dimensions of the Temperament and Character Inventory (TCI) and the NEO Personality Inventory. 8,9 These empirical studies suggest a close connection between human attachment and the characterization of personality, supporting Bowlby's 1 attachment theory with practical data.…”
Section: Introductionmentioning
confidence: 82%
“…They were recruited from medical students or staff in Yamagata University Hospital and its affiliated hospitals by KN, AS, TS, NT, and KO. Criteria of exclusion were 1) serious physical illnesses as clarified by a self-report checklist, 2) current or past history of psychiatric disorders of the Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV, as clarified by the psychiatric screening previously described, 4,25 and 3) parental divorce or death before the age of 16. The DSM-IV was used in this study, since the DSM-5 was not yet available in 2009 when the enrollment started.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…21 In line with this, our previous study suggests that a dysfunctional parenting style induces increased neuroticism. 22 On the other hand, it is shown that caregiver maltreatment induces increased BDNF gene methylation in prefrontal cortex, amygdala and hippocampus of rats. 23 In addition, individuals who received childhood abuse or low maternal care show increases in BDNF gene methylation in lymphocytes.…”
Section: Discussionmentioning
confidence: 99%